First evidence for Late Pleistocene to Holocene earthquake surface faulting in the Eastern Monferrato Arc (Northern Italy): Geology, pedostratigraphy and structural study of the Pecetto di Valenza site. (7th September 2017) - Frigerio, C.; Bonadeo, L.; Zerboni, A.; Livio, F.; Ferrario, M.F.; Fioraso, G.; Irace, A.; Brunamonte, F.; Michetti, A.M.
Abstract: The W Po Plain (Northern Italy) is commonly regarded as a region characterized by a low seismicity hazard, due to the lack of historical and instrumental record of strong earthquakes. Nevertheless, recent studies performed in the Monferrato hills provide evidence of active faulting and possible paleoseismicity occurred in Middle Pleistocene to Holocene times. Therefore, for verifying the seismic potential of this area, we firstly revised the available geological and geophysical information. We selected the area between Valenza and Alessandria (Eastern Monferrato Arc), which show the best structural, geomorphic, and stratigraphic setting for documenting recent tectonic deformation and faulting. Therein, we identified, for the first time, evidence for earthquake surface displacement in a Late Quaternary pedosedimentary sequence exposed at Pecetto di Valenza. The outcropping section has been logged and investigated according to an approach integrating sedimentological and micropedological data with structural analyses and radiocarbon dating. This allowed reconstructing the recent surface evolution and the paleoseismic history of the site. From the bottom, the pedosedimentary sequence consists of a Miocene marly bedrock, whose weathering started in Marine Isotopic Stage (MIS) 7 or 5 interglacials. A colluvial deposit follows, whose formation can be attributed to MIS 5e. The upper part of the sequence consists of two loess covers, showing different degrees of weathering, possibly occurred at ca. 30 ka BP for the deepest loess and in the Middle Holocene (ca. 4 ka BP) for the uppermost one. The loess accretion is therefore older and likely associated to the MIS 3 and MIS 2 glacial phases. Each deposit records the deformation induced by earthquake surface reverse faulting and warping, giving constraints to the sequence of events that characterized this site. In fact, the structural analyses and a 2D balanced retrodeformation of the section, integrating pedostratigraphic constraints, allowed identifying at least two different phases of deformation, and more than five fault scarp-forming events, which caused a total net displacement of ca. 4.8 m during the past ca. 40 ka. Our approach highlighted the interaction between the tectonically induced surface deformation and the aeolian deposition, allowing reconstructing the recent evolution of a small drainage basin. The results of this paleoseismic analysis reinforce the conclusion of previous Authors that the Monferrato Arc should be viewed as a seismic gap, characterized by strong earthquakes (Mmax ∼6.5) with long recurrence interval (in the order of several thousands years). This evidence has relevant implications for seismic hazard assessment, which must be checked with further trench investigations along the mapped Quaternary thrust faults affecting the western part of the Po Plain.